2022
DOI: 10.1038/s41598-022-21864-3
|View full text |Cite|
|
Sign up to set email alerts
|

Deciphering sex-specific miRNAs as heat-recorders in zebrafish

Abstract: In the last decade, a plethora of microRNAs (miRNAs) has been reported in a wide variety of physiological processes, including reproduction, in many aquatic organisms. However, miRNAome alterations occurred by environmental cues due to water temperature increment have not yet been elucidated. With the aim to identify epigenetic regulations mediated by miRNAs in the gonads in a climate change scenario, the animal model zebrafish (Danio rerio) were subjected to high temperatures during sex differentiation, a tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
0
4
1
Order By: Relevance
“…Indeed, regarding Experiment 1, cancer does not appear to be associated with differential sex-specific mortality at the embryonic stage, nor does it play a role in sex determination (since both phenomena would have skewed the sex-ratio). These results contrasts with numerous studies that have identified sex-specific responses in zebrafish regarding various factors (e.g., (Zhou et al 2010, Li et al 2019, Giommi et al 2022, Lin et al 2022, Park et al 2022, van Gelderen et al 2022, Zhai et al 2022, Zheng et al 2022, Zhong et al 2023)), including cancers (e.g., (Lee et al 2018, 2021, Mensah et al 2019, Montal et al 2023)). One possible explanation is that the cancer type used in our study may have too low aggressiveness, as possibly evidenced by the ability of individuals affected at the embryo stage to develop into adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, regarding Experiment 1, cancer does not appear to be associated with differential sex-specific mortality at the embryonic stage, nor does it play a role in sex determination (since both phenomena would have skewed the sex-ratio). These results contrasts with numerous studies that have identified sex-specific responses in zebrafish regarding various factors (e.g., (Zhou et al 2010, Li et al 2019, Giommi et al 2022, Lin et al 2022, Park et al 2022, van Gelderen et al 2022, Zhai et al 2022, Zheng et al 2022, Zhong et al 2023)), including cancers (e.g., (Lee et al 2018, 2021, Mensah et al 2019, Montal et al 2023)). One possible explanation is that the cancer type used in our study may have too low aggressiveness, as possibly evidenced by the ability of individuals affected at the embryo stage to develop into adulthood.…”
Section: Discussioncontrasting
confidence: 99%
“…Although DNA methylation changes with age provides a strong foundation for the development of epigenetic clocks, consideration could perhaps be paid to other epigenetic mechanisms or modifications such as histone modifications and, specially, noncoding RNAs (ncRNAs), including micro-RNAs (miRNAs) (van Gelderen et al, 2022). In particular, quantifying levels of miRNAs is relatively easy (Lee and Shin, 2012).…”
Section: Epigenetic Changes With Agementioning
confidence: 99%
“…Other studies in zebrafish describing the heat stress by temperature in the gonadal miRNome revealed that miR-22b and miR-301a were altered to be fully recovered three months after the exposure (Ikert and Craig, 2020). In zebrafish females, 23 miRNAs were DE in ovaries after larval heat-treatment, among which, for example, dre-miR-726-3p was downregulated while dre-miR-724-5p was upregulated (van Gelderen et al, 2022). Interestingly, these two miRNAs were both found to be downregulated in E. sea bass testis one year after heat exposure in the present study, indicating that a conservation in the heat response among species may exist.…”
Section: Discussionmentioning
confidence: 99%
“…In the Antarctic notothenioid ( Trematomus bernacchii ), adapted to extreme climates of temperatures around −1°C, an acute heat stress was able to alter 12 miRNAs in the gills, mainly pertaining to cellular stress response (Vasadia et al, 2019). Long-term effects on the miRNome were shown in zebrafish ( Danio rerio ) (van Gelderen et al, 2022) and in Atlantic cod (Bizuayehu et al, 2015). Further, adult zebrafish exposed to high temperature for 21 days changed the miRNome with a consecutive recovery in which miRNA expressions returned to their original state (Ikert and Craig, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation